A Phenomenological Study of Domestic Violence and Its Impact on Women's Psychological and Reproductive Health in Solok City, Indonesia - Novi Wulan Sari; Evi Hasnita; Erit Rovendra; Rahmi Sari Kasoema (Bulletin of Inspiring Developments and Achievements in Midwifery, 2025)
Domestic violence (DV) in Indonesia is rising, with over 400,000 cases reported in 2022, driven by increased public awareness post the Domestic Violence Elimination Act, yet communities often limit it to physical abuse, ignoring psychological and reproductive health effects. This study explores lived experiences of DV among women in Solok City and its impacts on their psychological and reproductive health. A qualitative phenomenological approach involved eight women recruited via snowball sampling, with data from 45–60-minute in-depth interviews and documentation, ensuring trustworthiness through prolonged engagement and triangulation. All participants (100%) faced multiple violence forms: six physical, seven psychological, and five forced sexual activity. Psychological effects included chronic stress (7/8), sleep disturbances (5/8), shame (6/8), and depressive symptoms (5/8). Reproductive issues affected five with menstrual irregularities, four with recurrent vaginal infections/discharge, and three with reduced libido, linked to prolonged violence, financial stress, and overwork causing hormonal disruptions. DV profoundly impairs women's psychological and reproductive health in Solok City, underscoring needs for heightened community education, expanded support services, accessible reporting, and empowering women to reject violence and seek help.